Design of healable epoxy composite based on β-hydroxyl esters crosslinked networks by using carboxylated cellulose nanocrystals as crosslinker. (8th September 2019) - Xu, Chuanhui; Zheng, Zhongjie; Wu, Wenchao; Fu, Lihua; Lin, Baofeng
Abstract: Thermosetting resin-based composites are applied widely, but they are insoluble and infusible once complete curing so that they may be wasteful when the materials have some damages. Here, we use a simple and efficient method to design an epoxy composite which can be healed and recycled via interesterification reaction at elevated temperature. Carboxylated cellulose nanocrystals (CCNs) with a large number of carboxyl groups on the surface were isolated from cotton by hydrochloric acid and nitric acid, and then were used as crosslinker to react with diglycidyl ether of bisphenol A (DGEBA). Fourier transform infrared (FTIR) spectroscopy result indicates that β-hydroxyl ester bonds were formed between carboxyl groups and epoxy groups, while the equilibrium swelling experiment result confirms the formation of β-hydroxyl ester bond-crosslinked networks. Interestingly, the char yields of composites (>16%), much higher than that of CCNs (7.05%) and DGEBA (4.44%), were about three times higher than the calculated values, showing a significantly improved thermal stability. It was found that the composite with a carboxyl/epoxy = 0.2 has a better and more obvious healing affect at 180 °C than others. Graphical abstract: Image 1